MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR AQIDAH AKHLAQ MATERI PERILAKU AKHLAQ TERPUJI MELALUI STRATEGI SNOWBALL THROWING PESERTA DIDIK KELAS VIII B MTS NAHDLATUL ULAMA’ KRAKSAAN PROBOLINGGO - Naili Fathimatuz Zakiyyah; Ainol (al-Afkar, Journal For Islamic Studies, 2022)
The purpose of this article is to discuss a study in increasing the activity and learning outcomes of aqidah akhlaq material for commendable moral behavior through a snowball strategy for class VIII B students of MTs Nahdlatul Ulama' Probolinggo district in the odd semester of 2021/2022. Because seeing the reality of initial observations at MTs Nahdlatul Ulama', only a small number were active and learning outcomes were low, the researchers tried to use the right aqidah akhlaq learning strategy, namely the snowball throw method. This research is in the type of CAR which has two, each cycle has four stages. The subject of this research is class VIII B which opens 19 students. Researchers in this study collect data by observation, documentation, and tests. This study uses data analysis techniques for comparison between cycles 1 and 2 with increased activity and learning outcomes of aqidah akhlaq material for commendable akhlaq behavior using the snowball throwing strategy for class VIII B students of MTs Nahdlatul Ulama'. It can be seen that the learning activity data on the percentage of pre-cycle, cycle 1 and 2 increased in every qualification of all aspects. Learning outcomes also increased in students, namely pre-cycle with a completeness value of 31.6%, then cycle 1 with a completeness score of 65% (good enough) and cycle 2, namely 81.84 with a completeness value of 85% (good).